Pharmacokinetics of Orally Administered Prednisolone in Alpacas - Videla, Ricardo; Sommardahl, Carla; Smith, Joe; Schaefer, Deanna M. W.; Cox, Sherry (Frontiers in Veterinary Science, 2021)
Thjs study aimed to determine the pharmacokinetics of prednisolone following intravenous and oral administration in healthy adult alpacas. Healthy adult alpacas were given prednisolone (IV, n = 4), as well as orally (PO, n = 6). Prednisolone was administered IV once (1 mg/kg). Oral administration was once daily for 5 days (2 mg/kg). Each treatment was separated by a minimum 4 month washout period. Samples were collected at 0 (pre-administration), 0.083, 0.167, 0.25, 0.5, 0.75, 1, 2, 4, 8, 12, and 24 hours after IV administration, and at 0 (pre-administration), 0.25, 0.5, 0.75, 1, 2, 4, 8, 12, 24 after the first and 5th PO administration. Samples were also taken for serial complete blood count and biochemistry analysis. Prednisolone concentration was determined by high pressure liquid chromatography. Non-compartmental pharmacokinetic parameters were then determined. After IV administration clearance was 347 mL/kg/hr, elimination half-life was 2.98 hours, and area under the curve was 2940 h*ng/mL. After initial and fifth oral administration elimination half-life was 5.27 and 5.39 hours; maximum concentration was 74 and 68 ng/mL; time to maximum concentration was 2.67 and 2.33 hours; and area under the curve was 713 and 660 hr*ng/mL. Oral bioavailability was determined to be 13.7%. Packed cell volume, hemoglobin, and red blood cell counts were significantly decreased 5 days after the first PO administration, and serum glucose was significantly elevated 5 days after the first PO administration. In conclusion, serum concentrations of prednisolone after IV and PO administration appear to be similar to other veterinary species. Future research will be needed to determine the pharmacodynamics of prednisolone in alpacas.